Multiple myeloma: practice patterns across Europe - Raab, Marc-Steffen (British journal of haematology, 2016)
Real-world data describing management of patients with multiple myeloma are limited. A European (Belgium, France, Germany, Italy, Spain, Switzerland, UK) observational chart review was conducted to address this. Physicians completed questionnaires for every patient seen during a 2-4-week observation period, regardless of treatment status. A total of 435 physicians completed 7635 cross-sectional chart reviews. Overall, 47% of patients were undergoing anti-tumour drug treatment, 42% had previously received ≥1 line of treatment and 12% had never received anti-tumour drug treatment. Of the patients treated by oncologists, onco-haematologists or internists, 95% received, or were expected to receive, at least one line of anti-tumour drug treatment, 61% received ≥2 lines of therapy and 38% received ≥3 lines. Except in the UK, the most commonly used induction therapies contained bortezomib (48%); lenalidomide was the most commonly used first-line maintenance therapy (45%) and second- and third-line agent overall (60% and 52% of patients at those lines, respectively). Bortezomib retreatment was used in 47% of patients who received it first line. Treatment patterns became more diverse with subsequent treatment lines. This study provides insight into real-world treatment patterns in Europe. While treatment practices are broadly similar across countries, some notable differences in the agents used exist.
Gesehen am 01.12.2017